The tail of the trinosaur - Causley, Charles (London: Jane Nissen Books, 2006)
An enormous container is delivered to the people of Dunborough. Inside, the Trinosaur which has been asleep for ninety million years (or thereabouts) is waking up. Suggested level: primary, intermediate
Keywords: Juvenile works